The impact of Fitness Center servicescape on individual behavior: The Mediating role of emotional response - Ong, Derek Lai Teik *; Yap, Wei Xin (Taylor & Francis Open Access, 2017)
This study assesses the impact of fitness centers’ servicescape on individual behavior, exploring the mediating role of the Emotional Response between servicescape dimensions and individual behavior amongst customers of the Malaysian fitness industry. Consumers place great emphasis on the surrounding environmental stimuli which facilitates engagement during active fitness activity. 200 samples were collected from six different Malaysian fitness franchises and questions focused mainly on members perceptions of servicescape and how this affects behavior. Multiple linear regression and mediation model analysis reveals positive direct effects of the Physical and Natural dimensions of servicescape on individual behaviour, whilst mediating effects of Emotional Response are present for indirect relationships of Social and Natural dimension on individual behaviour. The results of this study serve to help the management of the fitness centers’ servicescape which will encourage more members’ engagement during their fitness regime while improving word of mouth marketing through their increased satisfaction.